Performance assessment of aluminium composite material for automotive brake rotor - Maleque, Md. Abdul (Inderscience Enterprises Ltd., 2014)
Application of composite material for brake rotor has the potential to improve braking performance due to its attractive properties when compared to cast iron material. Aluminium composite has superior specific strength, higher coefficient of thermal expansion/heat dissipation rate with low mass density. These characteristics possess the tendency to influence undesirable conditions during braking. In this study, composite brake rotor was fabricated using stir casting process and performance assessment was conducted with a passenger car brake system setup. The rotor achieved 50% weight reduction and the braking result reveals that composite rotor exhibited uniform thermal trend with 25% heat dissipation rate for braking pressure within the range of 1.5–2.0 MPa over cast iron. The contour trend of cast iron rotor exhibited high temperature zone which gives rise to formation of intermittent hot spot which is detrimental to braking conditions. Simulation modelling analysis showed good agreement with actual operating test measurements. Conclusively, composites are commercially viable and feasible to replace the existing cast iron material. Keywords: brake rotor; composite; performance assessment; weight reduction; modelling; stir casting; heat dissipation.